2020
DOI: 10.12982/vis.2021.015
|View full text |Cite
|
Sign up to set email alerts
|

The sperm longevity and freezability in the modified BHSV extender of Thai Pradu-hangdum chicken

Abstract: Pradu-hangdum is a distinctive Thai native pure breed chicken. To conserve the pure breed of this chicken species, the artificial insemination was invested. The key to the highly successful output of this technique is high quality of semen. Hence, the objective of the present study is to characterize the Pradu-hangdam sperms and their longevity and freezability in the BHSV extender. The semen of the 30 randomized male chicken were collected. The macroscopic and microscopic examination were used to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…The mean semen volume of the 20-month-old Dang Surat rooster was 265±23 µl (Table 1). This accords with other Thai native roosters: 215±80 µl (range 80-500 µl) for Pradu-hangdum (Khunkaew et al, 2021); 282 ± 89 µl for one-year-old Thai red junglefowl (Polsang et al, 2022), 255 ± 90 µl 7-8-month old and 208 ± 60 µl for 10-11-month old Thai native roosters (Inyawilert et al, 2019). Semen volumes may be age dependent: Thai native rooster, 8-13 months of age were not significant but tended to be lower in younger roosters (Chotesangasa, 2001).…”
Section: Sperm Quality Assessmentsupporting
confidence: 85%
See 1 more Smart Citation
“…The mean semen volume of the 20-month-old Dang Surat rooster was 265±23 µl (Table 1). This accords with other Thai native roosters: 215±80 µl (range 80-500 µl) for Pradu-hangdum (Khunkaew et al, 2021); 282 ± 89 µl for one-year-old Thai red junglefowl (Polsang et al, 2022), 255 ± 90 µl 7-8-month old and 208 ± 60 µl for 10-11-month old Thai native roosters (Inyawilert et al, 2019). Semen volumes may be age dependent: Thai native rooster, 8-13 months of age were not significant but tended to be lower in younger roosters (Chotesangasa, 2001).…”
Section: Sperm Quality Assessmentsupporting
confidence: 85%
“…Poultry semen has a low volume at high concentration and contains about 4-6 billion spermatozoa/ml. In the Thai native chicken, Pradu-hangdum, Khunkaew et al (2021) reported the sperm concentration of 5.24±0.58 billion sperm/ml. The mean semen volume of the 20-month-old Dang Surat rooster was 265±23 µl (Table 1).…”
Section: Sperm Quality Assessmentmentioning
confidence: 99%